Association between tooth loss and upper gastrointestinal cancer: A 30‐year follow‐up of the Linxian Dysplasia Nutrition Intervention Trial Cohort - Su Zhang; Pei Yu; Jian‐Bing Wang; Jin‐Hu Fan; You‐Lin Qiao; Philip R. Taylor (Thoracic Cancer, 2019)
Background This prospective study investigated the association between tooth loss and upper gastrointestinal (UGI) cancer mortality in the Linxian Dysplasia Nutrition Intervention Trial Cohort. Methods Subjects were categorized into three groups according to age at baseline. No missing teeth and less or greater than median tooth loss in each group was defined as none, moderate, and severe, respectively. Hazard ratios (HRs) and 95% confidence intervals (95% CIs) were estimated using the Cox proportional hazard model. Results Through 30 September 2015, 541 esophageal squamous cell carcinoma (ESCC), 284 gastric cardia carcinoma (GCC), and 77 gastric non‐cardia carcinoma (GNCC) deaths occurred. In the six‐year follow‐up, severe tooth loss was associated with an increased risk of GCC mortality (HR 1.55, 95% CI 1.06–2.18). In the 15‐year follow‐up, moderate tooth loss increased the ESCC mortality risk by 58% (HR 1.58, 95% CI 1.06–2.35), while severe loss increased the GCC mortality risk by 30% (HR 1.30, 95% CI 1.03–1.64). In the 30‐year follow‐up, moderate tooth loss increased the risk of ESCC mortality (HR 1.34, 95% CI 1.01–1.76). In subjects aged < 55 at baseline and men, moderate tooth loss had 53% and 52% higher risks of ESCC mortality (HR<55 years 1.53, 95% CI 1.06–2.05; HRmen 1.52, 95% CI 1.01–2.28). No significant association was observed for GNCC in any subjects or subgroups. Conclusion Moderate tooth loss increased the risk of ESCC mortality, particularly in younger subjects and men. Severe tooth loss increased the risk of GCC mortality. Future studies are needed to confirm these findings.